রম্যসমগ্র - শাকুর, আবদুশ (ঢাকা : মাওলা ব্রাদার্স, 2003)
Complete set of humorous and satirical short stories by a 20th century author from Bangladesh.
Donated by Akbar Ali Khan
In Bengali.
Keywords: Short stories, Bengali; Bengali wit and humor; Bengali literature